Mythological Identity and The Reconstruction of Spiritual Values in the Legend of Ratu Roro Kidul - Damayanti, Fira Nur Vianingtias; Taum, Yoseph Yapi (Randwick International of Social Science Journal, 2024)
ABSTRACT This study explores the mythological identity of Ratu Roro Kidul, a prominent figure in Indonesian folklore, and its implications for local spirituality and culture. Drawing from Mircea Eliade’s concept of mythology as a narrative structure that connects humans to the sacred and Joseph Campbell’s notion of mythological heroes as symbols of cultural identity, the study employs genealogical myth analysis to examine the origins, variations, and roles of Roro Kidul’s myth across Indonesia. The research highlights two main versions of the myth: one linking Roro Kidul to the Majapahit Kingdom as a goddess protecting the Southern Ocean, and the other associating her with the Kingdom of Pajajaran, emphasizing her transformation into a queen of spirits. Both versions reflect the intertwining of spiritual and historical narratives, with Roro Kidul serving as a guardian of nature and a symbol of political legitimacy, especially in relation to the Mataram Sultanate. The study concludes that the myth of Roro Kidul not only represents local beliefs but also functions as a tool for understanding the connection between humans, nature, and the supernatural, while playing a key role in shaping social and political identities in Java. This research paves the way for further studies on the role of myth in the construction of power and cultural identity in Southeast Asia.